PERUBAHAN TUTUPAN LAHAN HUTAN DI WILAYAH DAERAH ALIRAN SUNGAI CITARUM HULU PROVINSI JAWA BARAT TAHUN 2009-2017 MENGGUNAKAN CITRA LANDSAT DAN SISTEM INFORMASI GEOGRAFIS - Siregar, Nissa Amalia; Atmosoemarto, Mulyadi; Supriono, Bambang (Universitas Nusa Bangsa, 2018)
Land use and land cover are important components in understanding the interaction of human activities with the environment. Forest management including planning and supervision in the Upper Citarum Watershed Area of West Java is very important to be done to prevent more severe forest degradation. The purpose of this study is to measure land use change from 2009, 2013 and 2017. This research method is to utilize remote sensing technology and geographic information system (GIS) and then compare 3 map of land cover change. The classification results show that the Citarum watershed area has 13 classes of land cover. The significant land cover change from 2009 to 2017 forest land cover decreased from 64,938.99 Ha to 43,268.00. The rice field land cover Â class is scattered throughout the upper Citarum watershed area. Bandung District, West Bandung District, Bandung City, Cimahi City, Sumedang District and a small part of Garut